THE USE AND ABUSE OF CRITIAS: CONFLICTING PORTRAITS IN PLATO AND XENOPHON*. (20th November 2014) - Danzig, Gabriel
<x content-type="archive" xml:space="preserve">Abstract</x> This paper aims to explain the very sharp contrast between the portraits of Critias found in Plato and Xenophon. While depicted as a monster in Xenophon's Hellenica, Critias is described with at most mild criticism in Plato's writings. Each of these portraits is eccentric in its own way, and these eccentricities can be explained by considering the apologetic and polemic aims each author pursued. In doing so, I hope to shed light not only on the relations between these portraits and the works that contain them, but also on the personal relations between Plato and Xenophon and their manner of expressing them in literary productions.